The Role Of Leaders In Organizational Culture On Performance Amid The Covid 19 Pandemic - Max Raja P Sinaga; Jajang Gunawijaya (Syntax Literate, 2022)
The role and challenges of leadership depend on how to understand the prevailing culture at BRI. In the traditional perspective, organizational culture is treated as an instrument or function that can be manipulated by leaders to help organizations adapt to the realities of the external environment. From a symbolic-interpretive perspective, organizational culture is seen as a social phenomenon. This study aims to uncover and analyze the values of the organizational culture and personal dimensions through the experiences of participants as research subjects related to the role of BRI leaders in developing organizational culture during the Covid-19 pandemic. The research method used is qualitative with an ethnographic approach. The problem to be answered can be obtained through observation and in-depth interviews with participants or research informants consisting of the leadership of the BRI KC Mabes TNI, Cilangkap, Jakarta Timur. The values of AKHLAK (Trust, Competent, Harmonious, Loyal, Adaptive, and Collaborative) are embodied in the company's operational activities. The role of the leader in interpreting and implementing the corporate culture at the branch level is well executed. The leadership capacity of BRI KC TNI Headquarters Cilangkap implementing a corporate culture during the Covid-19 pandemic can maintain and even increase the company's revenue or performance.